THE ROLE OF MODERN INFORMATION SYSTEMS AND TECHNOLOGIES IN ENSURING THE ECONOMIC SECURITY OF THE ENTERPRISE IN THE CONDITIONS OF THE DIGITAL ECONOMY - CHAIKOVSKA, Inna; TKACH, Taras; CHAIKOVSKYI, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the impact of end-to-end automation and digitization on the economy and economic security of the enterprise. The two-facetedness of this influence is established: as new opportunities and new threats and risks. Among the possibilities: optimization of work, improvement of interaction with clients and development of new business models, improvement of efficiency and productivity of work, personalization of the offer, study of innovative sources of income, etc. It has been established that modern information systems provide complex data management capabilities, which allows enterprises to use the power of their data. This includes the ability to collect, store and analyze vast amounts of data, enabling more informed decisions. They also offer robust reporting and visualization tools, allowing companies to understand and display complex data in a more accessible way. Technologies such as artificial intelligence (AI), machine learning (ML) and data analytics help to understand market trends, consumer behavior and competitive dynamics. They provide real-time monitoring of business operations, enabling quick decision-making and immediate response to threats and opportunities. Among the problems: in the Digital economy, enterprises are exposed to a wide range of risks that can have a significant impact on their economic security. These risks can come from many different sources, such as cyber threats, technology disruptions and market volatility. The work proposes to form a digital ecosystem as a component of the economic security of the enterprise in order to ensure the economic security of the enterprise in the conditions of the Digital economy. This digital ecosystem should combine the use of the latest technologies (artificial intelligence, machine learning, cloud computing, big data analytics, predictive modeling, augmented and virtual reality, industrial Internet of Things) together with the latest information systems (ERP, HRM, MES, CRM, PRM, SCM, etc.) for the purpose of collecting, storing, processing and disseminating information regarding various aspects of the economic security of the enterprise. This information will contribute to the active detection, analysis, and assessment of the impact of risks on the operation of the enterprise in the conditions of the Digital economy, as well as to the adoption of an effective, substantiated management decision for the purpose of risk management (management, information, personnel, technological, etc.). This approach will allow to increase the level of economic security of the enterprise under the conditions of digitalization.
Keywords: Digital economy; digitization; information technologies; information systems; economic security of the enterprise; Artificial Intelligence